1995
DOI: 10.1101/gr.5.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and RARE cleavage mapping of human 2p, 6q, 8q, 12q, and 18q telomeres.

Abstract: Large terminal fragments of human chromosomes 2p, 6q, 8q, 12q, and 18q were cloned using yeast artificial chromosomes (YACs). RecA-assisted restriction endonuclease {RARE] cleavage analysis of genomic DNA samples from II unrelated individuals using YAC-derived probes confirmed the telomeric localizations of the half-YACs studied. The cloned fragments provide telomeric closure of maps for the respective chromosome arms and will supply the reagents needed for analyzing and sequencing these distal subtelomeric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
1
21
1
1
Order By: Relevance
“…Data on polymorphic telomeres are from Riethman, unpubl. results;Wilke et al (1991); Ijdo et al (1992); Cook et al (1994); Macina et al (1994Macina et al ( , 1995; Martin-Gallardo et al (1995); Reston et al (1995); Monfouilloux et al (1998);Trask et al (1998);van Overveld et al (2000). sequences were not already identified by the BLAST analysis described above; for the most part, the regions identified by WSSD were consistent with our analyses, although each method missed a small percentage of the duplications.…”
Section: Sequence Organization Of Subtelomeric Dnasupporting
confidence: 80%
See 1 more Smart Citation
“…Data on polymorphic telomeres are from Riethman, unpubl. results;Wilke et al (1991); Ijdo et al (1992); Cook et al (1994); Macina et al (1994Macina et al ( , 1995; Martin-Gallardo et al (1995); Reston et al (1995); Monfouilloux et al (1998);Trask et al (1998);van Overveld et al (2000). sequences were not already identified by the BLAST analysis described above; for the most part, the regions identified by WSSD were consistent with our analyses, although each method missed a small percentage of the duplications.…”
Section: Sequence Organization Of Subtelomeric Dnasupporting
confidence: 80%
“…Large variant alleles of many human subtelomeric regions exist, and are believed to consist entirely of subtelomeric repeats (Wilkie et al 1991;Macina et al 1994Macina et al , 1995Trask et al 1998;Mefford and Trask 2002). For example, Wilkie et al (1991) found that three alleles varying in length up to 260 kb exist at the 16p telomere.…”
mentioning
confidence: 99%
“…Because the presence/absence of fluorescent signals indicates the gain/loss of segments that are several tens of kilobases long, this variability is most probably related to size polymorphisms known to affect some chromosome ends (Brown et al 1990). For instance, the relatively rare 6qter-DNF92 variant P observed here may correspond to, and perhaps completely explain, the long 6qter allele described by Macina et al (1995). Similarly, the four 16pter variants distinguished here by FISH techniques may be related to the length polymorphism found for this chromosome end (Wilkie et al 1991).…”
Section: Discussionmentioning
confidence: 92%
“…The commercial 2ptel probe (Vysis) is obtained by Alu-PCR from the 340 kb half-YAC clone yRM2052, presumably containing the terminal 320 kb of chromosome 2p, as one of its ends (U32389) maps at chr2:322536 -322595. 12 As telomeric FISH markers can be located even at 300 -400 kb proximal to the telomeric end, we postulated that the preservation of tel2p probe signals could represent either a single-copy region between the duplicated portion and a more distal deleted region or the start point of the duplicated region. Further experiments demonstrated that the second alternative was correct: the probe overlaps both the deleted segment and a portion of the duplicated sequence.…”
Section: Discussionmentioning
confidence: 99%